2018
DOI: 10.1186/s12974-018-1054-3
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation mediates chronic mild stress-induced depressive- and anxiety-like behavior in adult rats

Abstract: BackgroundDepression is a heterogeneous disorder, with the exact neuronal mechanisms causing the disease yet to be discovered. Recent work suggests it is accompanied by neuro-inflammation, characterized, in particular, by microglial activation. However, microglial activation and its involvement in neuro-inflammation and stress-related depressive disorders are far from understood.MethodsWe utilized multiple detection methods to detect the neuro-inflammation in the hippocampus of rats after exposure to chronic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
225
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(249 citation statements)
references
References 53 publications
19
225
2
3
Order By: Relevance
“…It has been suggested that chronic stress increased gene expression of some inflammatory factors in the hippocampus such as IL-1b, IL-18, and IL-6. IL-1b is an important mediator of stress-induced anxiety-like behavior and it has been reported that the hippocampal IL-1b mRNA was upregulated in stressed rats (Jones et al, 2018;Wang et al, 2018). More importantly, the mature form of IL-1b as well as its convertase, cleaved caspase-1, were both increased in the hippocampus after exposure to chronic stress .…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that chronic stress increased gene expression of some inflammatory factors in the hippocampus such as IL-1b, IL-18, and IL-6. IL-1b is an important mediator of stress-induced anxiety-like behavior and it has been reported that the hippocampal IL-1b mRNA was upregulated in stressed rats (Jones et al, 2018;Wang et al, 2018). More importantly, the mature form of IL-1b as well as its convertase, cleaved caspase-1, were both increased in the hippocampus after exposure to chronic stress .…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the acute stress models shown in this figure, unpredictable chronic mild stress (UCMS) is delivered for prolonged periods of 8-12 weeks and includes once daily, for example, immobilization, food deprivation, light/dark phase reversal, hot environment, and cage shaking. This procedure leads to depressive-like behavior as measured by reduced sucrose consumption and prolonged immobility in the tail suspension test (TST) and forced swim test (FST) in rodents (Zhang et al, 2015;Su et al, 2017;Wang et al, 2018;Feng et al, 2019). UCMS also resulted in higher protein levels of NLRP3, caspase-1, and IL-1β in the hippocampus of stress-exposed mice (Zhang et al, 2015) and rats (Wang et al, 2018;Feng et al, 2019).…”
Section: The P2x7r Triggers Neuroinflammation and Subsequent Mood Dismentioning
confidence: 99%
“…This procedure leads to depressive-like behavior as measured by reduced sucrose consumption and prolonged immobility in the tail suspension test (TST) and forced swim test (FST) in rodents (Zhang et al, 2015;Su et al, 2017;Wang et al, 2018;Feng et al, 2019). UCMS also resulted in higher protein levels of NLRP3, caspase-1, and IL-1β in the hippocampus of stress-exposed mice (Zhang et al, 2015) and rats (Wang et al, 2018;Feng et al, 2019). Pharmacological blockade of NLRP3 (Zhang et al, 2015) or its genetic deletion (Su et al, 2017) decreased the level of inflammatory mediators and counteracted the symptoms of depressive-like behavior.…”
Section: The P2x7r Triggers Neuroinflammation and Subsequent Mood Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, animals exposed to this paradigm do not uniformly develop depressive‐like behaviors; those who are “stress susceptible” (the majority of animals) show increases in inflammation‐related microglia gene expression, whereas “resilient” animals show activation of gene transcripts implicated in cellular and behavioral plasticity to stress (Lehmann et al, ). Chronic unpredictable stress also induces microglial activation which mediates stress effects on anxiety and depressive‐like behavior (Wang et al, ). Prenatal and early life stress exposure lead to elevated microglial activity (Calcia et al, ), which may persist over time and have long‐term consequences for neural function, mood, and cognition (Bilbo & Schwarz, ).…”
Section: Interactions Between the Nervous System And The Immune Systementioning
confidence: 99%